(untitled) (Bioscience Journal, 2017)
The psychrotrophic bacteria growth in refrigerated milk is responsible for the production of heat resistant enzymes, including those which have lipolytic capacity. Lipases can cause rancidity and off-flavor in pasteurized and UHT milk, milk powder and cheese. Pseudomonas spp. is the major genera responsible by lipases synthesis, mainly Pseudomonas fluorescens. The lipolytic capacity of Pseudomonas spp. (1182 strains) and P. fluorescens (158 strains) isolated from cooling tank and bulk milk transportation were tested. Pseudomonas spp. strains were isolated by Pseudomonas Agar Base, adding the supplement cephalotin, fusidic acid, cetrimide- CFC (30º C/48 h) and Pseudomonas Cetrimide Agar with 10% of glicerol (21º C/ 48 h) to determine P. fluorescens. The strains lipolytic capacity were tested with Tributyrin Agar (21 oC/72 h). Lipolytic indexes of Pseudomonas spp. were 51.4% and 67.2% in cooling tank and bulk milk transportation (p< 0.05), respectively. P. fluorescens lipolytic capacity indexes were 26.4% from strains isolated from cooling tank and 41% (p < 0.05) from strains isolated from bulk milk transportation. High lipolytic indexes had been found in the strains isolated from refrigerated raw milk sent to manufacturing. Refrigeration temperature and storage time may contribute to the difference observed between two points of collection evaluated in this study.